2011
DOI: 10.1080/00071668.2010.540230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wet feeding on growth performance of broiler chickens in a hot climate

Abstract: 1. The Guinea Savanna in the tropics is characterised by high diurnal temperatures, often beyond the thermo-neutral zone of modern poultry, which imposes heat stress on them. 2. An experiment was conducted to determine the effect of partially (12 h wet mash in the day and 12 h dry mash in the night) or wholly (24 h) feeding wet mash on the growth performance of broiler chickens. 3. Three treatments: dry mash (control), wet mash (day) + dry mash (night) and wet mash (day + night) were tested. At 28 d of age, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Also, it may be due to allow more fast penetration of digestive juices by these changes in physical parameters of the feed form (Frikha, et al, 2009). The results of this experiment were supported by Yalda and Forbes, (1995), Ogbonna et al, (2001), Awojobi and Meshioye (2001), Awojobi et al, (2009 and2011) and Dei and Bumbie, (2011) who reported that wet feed was more beneficial and improved growth rate than mash or dry feed. Akinola et al, (2015) found a significant higher BWG for chickens fed wet feed.…”
Section: Results and Discussion 1-body Weight (Bw) And Gain (Bwg)supporting
confidence: 74%
“…Also, it may be due to allow more fast penetration of digestive juices by these changes in physical parameters of the feed form (Frikha, et al, 2009). The results of this experiment were supported by Yalda and Forbes, (1995), Ogbonna et al, (2001), Awojobi and Meshioye (2001), Awojobi et al, (2009 and2011) and Dei and Bumbie, (2011) who reported that wet feed was more beneficial and improved growth rate than mash or dry feed. Akinola et al, (2015) found a significant higher BWG for chickens fed wet feed.…”
Section: Results and Discussion 1-body Weight (Bw) And Gain (Bwg)supporting
confidence: 74%
“…[4][5][6] The thermoneutral zone for poultry is 18°C-24°C in the tropics 112 singh et al and 12°C-26°C in the temperate zones, but this often gets exceeded in the tropics, resulting in heat stress. 7,8 By elevating circulatory corticosteroids and decreasing thyroid activity, heat stress impairs broiler performance, especially in adult birds, because the ability to dissipate heat decreases with age. 9,10 Drastic decline in feed intake occurs in heat-stressed birds as a physiological response to minimize intrinsic heat production and to maintain the thermal homeostasis, thus bringing down feed efficiency, live weight gain, and survival rates.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize body weight gain and feed utilization for broilers, the environmental temperature should be near 21°C (Cooper and Washburn, 1998). In fact, it was found that there was a significant correlation with growth rate and the diurnal fluctuation in cloacal temperature (Cooper and Washburn, 1998) and that the growth rate and feed consumption of birds raised in higher environmental temperatures were depressed (Dei and Bumbie, 2011). Additionally, the present ginger (Zingiber officinale Roscoe) is known for its strong flavor and to have pyrogenicity (Eldershaw et al, 1992;Fujisawa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%